2018
DOI: 10.1021/acscatal.8b03563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of a Conformationally Mobile Peptide-Based Catalyst for Atroposelective Bromination

Abstract: It is widely accepted that structural rigidity is required to achieve high levels of asymmetric induction in catalytic, enantioselective reactions. This fundamental design principle often does not apply to highly selective catalytic peptides that often exhibit conformational heterogeneity. As a result, these complex systems are particularly challenging to study both experimentally and computationally. Herein, we utilize molecular dynamics simulations to investigate the role of conformational mobility on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 83 publications
2
39
0
Order By: Relevance
“…Second, it exhibits high degrees of selectivity despite the use of a highly‐fluxional chiral catalyst. This is contrary to the conventional view that highly selective catalysts should be fairly rigid, raising fundamental questions regarding the interplay of catalyst flexibility and selectivity . Finally, Sibi et al .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Second, it exhibits high degrees of selectivity despite the use of a highly‐fluxional chiral catalyst. This is contrary to the conventional view that highly selective catalysts should be fairly rigid, raising fundamental questions regarding the interplay of catalyst flexibility and selectivity . Finally, Sibi et al .…”
Section: Introductionmentioning
confidence: 90%
“…This is contrary to the conventional view that highly selective catalystss hould be fairly rigid, raising fundamentalq uestions regarding the interplay of catalyst flexibility and selectivity. [36,37] Finally, Sibi et al [28] observed that biaryl alcohols with electronrich substituents at the b'-position exhibit much higher selectivitiest han those with electron-poor ones. Although this was explained in terms of ap ossible non-covalent interaction betweenthese substituents and the N-acyl group, the established precedento fp···p + interactions in similara cylation reactions [32][33]35] raises the possibility that these substituent effects are due to the modulation of p···p + interactions in the stereochemistry-controllingtransition state (TS).…”
Section: Introductionmentioning
confidence: 99%
“…Computational approaches, particularly multivariate linear regression tools and molecular dynamics simulations have been used to further study the atroposelective bromination of quinazolinones. 53…”
Section: Peptide Catalystsmentioning
confidence: 99%
“…6a ,6c, 7a One strategy to potentially address this challenge and gain insight into key structural features that influence selectivity is to develop structure-function relationships through the application of modern physical organic tools to relate the reaction output(s) to computed structural parameters. 53a ,55…”
Section: Peptide Catalystsmentioning
confidence: 99%
See 1 more Smart Citation